Analisis Strategi Lokasi terhadap Tingkat Daya Tarik Masyarakat di EJ33 Avenue Tarakan - Hidayat, Nurul; Arun Dzaki, Haidar; Wirawan, M. Riyu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Location strategy is a critical factor in the success of a coffee shop business. The cafe / coffee shop business relies heavily on strategic locations to attract customers and maximize profitability. This article discusses various aspects of the location strategy for the coffee shop and external factors that affect visitor attraction to EJ33 Avenue in Tarakan City. This study aims to determine the effect of location strategy on buying interest EJJ3 Avenue in Tarakan. This study uses a quantitative approach. The sample was taken using Purposive Sampling, namely sampling with certain considerations and based on the objectives of the researcher, which amounted to 0 respondents. The sample was filled by Tarakan City people who had visited, shopped, and knew about EJ33 Avenue in Tarakan City. Data analysis method used is multiple linear regression analysis and SPSS testing 26. Based on the results of this study, the location strategy affects the interest in visiting EJ33 Avenue in Tarakan City. This is based on the results of tests conducted to see the indirect effect of the location on consumer buying interest EJ33 Avenue. Coffee shops can develop strong location strategies that can help them achieve long-term success. It can be concluded that consumer buying interest can arise due to the influence of the location offered by the coffee shop, thus attracting the interest of consumers to visit.